2015
DOI: 10.1097/bpo.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

Subaxial Cervical Spine Injuries in Children and Adolescents

Abstract: Level IV-retrospective, diagnostic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…While the majority of the studies from the West report that the most common mechanism of injury is motor vehicle accidents in younger children and sports-related activities in older children [12,13,14,15], our series noted that the most common mechanism of injury was trivial fall in younger children and fall from height in older children. This probably indicates that the children are less exposed to high-velocity motor vehicle injuries in our population.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…While the majority of the studies from the West report that the most common mechanism of injury is motor vehicle accidents in younger children and sports-related activities in older children [12,13,14,15], our series noted that the most common mechanism of injury was trivial fall in younger children and fall from height in older children. This probably indicates that the children are less exposed to high-velocity motor vehicle injuries in our population.…”
Section: Discussionmentioning
confidence: 82%
“…Patients with complete cord injury were not considered for surgery at the acute period. Most series from the West have reported a similar proportion of surgical intervention in their cohorts [14,21]. Dogan et al [21], in their series, reported that surgical management was offered in older children and children under 8 years did not require surgical intervention.…”
Section: Discussionmentioning
confidence: 97%
“…It is estimated that only 1% of all pediatric injuries involve the cervical spine. [1][2][3][4][5][6] Compared with adult cervical spine injuries, sports injuries are more common in the adolescent patient, because of a higher level of activity and greater risk proclivity. 1,3,5,[12][13][14] The most common mechanism of injury is blunt trauma.…”
Section: Epidemiology and Injury Characteristicsmentioning
confidence: 99%
“…11,12 Concordant to other injuries in the pediatric patient population, boys are more likely to be involved, with a sex ratio of 1.5-2:1. [1][2][3][4][5][6] Pediatric patients are especially at risk for a CSI because of the disproportionate size of the head compared with the body. Motor vehicle accidents cause >50% of PCSI, and most victims are the car occupants (31%-42%); however, victims may also be struck by a car while walking (11%-16%) or riding a bicycle (5%).…”
Section: Epidemiology and Injury Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation